Suicidal Attempt in Bipolar Disorder:Low Significance of Comorbidity with Opioid Dependence - Morteza Naserbakht; Azizeh Afkham Ebrahimi; Hajar Ahmadi Vazmalaei; Atefeh Ghanbari Jolfaei; Amir Shabani (Iranian Journal of Psychiatry, 2009)
Objectives: The relationship between suicidal attempt and opioid use disorder in patients with bipolar disorder (BD) is unknown. This study aimed at shedding some light on this issue. Method:178 inpatients aged 18-65 with BD type I with or without opioid use disorders were face-to-face interviewed through the Persian Structured Clinical Interview for DSM-IV axis I disorders (SCID-I), the Global Assessment of Functioning (GAF) scale, and a questionnaire including demographic and some clinical factors. Results:Gender was the only demographic factor with a statistical significant difference between suicidal and non-suicidal bipolar patients. Also, comorbidity with anxiety disorders and the type of index and current mood episodes were significantly different between the two groups (p<0.05). But after using a logistic regression analysis, the only statistical significant different factors (p<0.05) between the two groups were gender, comorbidity with anxiety disorders, and GAF. Conclusion:Opioid dependence comorbidity can not be considered as a risk factor for suicidal attempt in patients with BD.